Sclerosing cholangitis following severe trauma: Description of a remarkable disease entity with emphasis on possible pathophysiologic mechanisms - Benninger, Johannes (World J Gastroenterol, 2005)
AIM: Persistent cholestasis is a rare complication of severe trauma or infections. Little is known about the possible pathomechanisms and the clinical course. METHODS: Secondary sclerosing cholangitis was diagnosed in five patients with persistent jaundice after severe trauma (one burn injury, three accidents, one power current injury). Medical charts were retrospectively reviewed with regard to possible trigger mechanisms for cholestasis, and the clinical course was recorded. RESULTS: Diagnosis of secondary sclerosing cholangitis was based in all patients on the primary sclerosing cholangitis (PSC)-like destruction of the intrahepatic bile ducts at cholangiography after exclusion of PSC. In four patients, arterial hypotension with subsequent ischemia may have caused the bile duct damage, whereas in the case of power current injury direct thermal damage was assumed to be the trigger mechanism. The course of secondary liver fibrosis was rapidly progressive and proceeded to liver cirrhosis in all four patients with a follow-up >2 years. Therapeutic possibilities were limited. CONCLUSION: Posttraumatic sclerosing cholangitis is a rare but rapidly progressive disease, probably caused by ischemia of the intrahepatic bile ducts via the peribiliary capillary plexus due to arterial hypotension. Gastroenterologists should be aware of this disease in patients with persistent cholestasis after severe trauma.